(Non)conferences EdCamp Ukraine as an effective way of the teachers’ qualification improvement in Ukraine - Druhanova, Olena; Ipolitova, Daryna (Scientific notes of the pedagogical department, 2022)
The purpose of the article is analyzing the experience of the teachers’ qualification improvement in Ukraine nowadays using the example of EdCamp (non)conferences. In the process of writing the article, theoretical (analysis, synthesis, generalization etc.) and empirical (interviewing) methods were used. It was proved that the problem of the teachers’ qualification improvement has always been the subject of leading national educators’ and educational politicans’ attention. Over a considerable period of time, various forms of postgraduate pedagogical education have been accumulated in the national educational space - from courses and congresses, dated to the second half of the 19th century, to various retraining and advanced training faculties of a number of higher education institutions, in particular institutes of postgraduate pedagogical education (IPPЕ), research institutes etc. EdCamp has become widespread in Ukraine in recent years. EdCamp is the community of responsible teachers, which is not actually Ukrainian practice, but was borrowed from abroad. It has been established that EdCamp is a relatively new subject of the qualification improvement that immediately won its audience in Ukraine. The article summarizes the experience of the (non)conferences organized by this organization during the period of 2015-2022. The pages of the study also present the results of an interview of an active participant of both national (4 times) and mini- and affiliated EdCamps (7 times), a biology teacher of the Pervomaisky lyceum №2, Lozova district, Kharkov region, a headmaster of the MI “Center of Professional Development of Pedagogical Workers” in Pervomaisky Bihun Olga Oleksandrivna. The list of questions that were asked to the respondents included:How did you get to EdCamp?How is the event organized?What is the issue of the (non)conference?What are your impressions?